Pengaruh CSR, Struktur Modal, dan Laju Inflasi pada Nilai Perusahaan Manufaktur BEI - Alvin Rofiqie; Sodik; Hartini Prasetyaningsih Pawestri (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of Corporate Social Responsibility (CSR), capital structure, and inflation on firm value in manufacturing companies listed on the Indonesia Stock Exchange during 2019–2023. Firm value is a key indicator of investor perception regarding a company's prospects. The three variables were chosen to represent internal and external factors affecting firm value. The research method employed multiple linear regression using SPSS software, along with classical assumption tests. The results show that partially, CSR and inflation do not significantly affect firm value, while capital structure has a significant influence. Simultaneously, all three variables significantly affect firm value according to the F-test. The findings imply that investors prioritize optimal capital structure over CSR practices and inflation impacts. Thus, a combination of internal and external factors should be considered when assessing firm value, particularly in the manufacturing sector.